Recommendations for (Pharmaco)Genetic Sampling in Patients Following Allogeneic Hematopoietic Stem Cell Transplantation - Anniek Bokma; Maja Matic; Arwin Ralf; Bianca J. C. vanden Bosch; Manfred Kayser; Ron H. N. vanSchaik; Melvin Lafeber; Marieke J. H. Coenen; Florence Atrafi (Clinical and Translational Science)
ABSTRACT In patients receiving allogenic hematopoietic stem cell transplantation (aHSCT) complete chimerism is desired. However, this brings a challenge when non‐invasive assessment of recipient germline DNA is required for genetic testing. Here, we aim to create awareness for (pharmaco)genetic sampling in patients following aHSCT based on a case report of a patient following aHSCT in which pharmacogenetic analysis was performed. Six pharmacogenetic genes were analyzed in DNA extracted from peripheral blood (pre‐ and post‐transplant), buccal swab, and hair follicles. To investigate the presence of donor DNA in post‐transplant samples, short tandem repeat and digital droplet PCR analysis were performed. DNA from post‐transplantation peripheral blood and the buccal swab showed identical genotypes: CYP2C9*1/*1, CYP2C19*1/*2, CYP2D6*2/*9, CYP3A4*1/*1, VKORC1‐1639TT, SLCO1B1*1/*5. Pre‐transplant DNA showed different genotypes for CYP2D6 (*1/*2) and SLCO1B1 (*1/*1). Due to the low DNA amount extracted from hair follicles, only CYP2D6 and SLCO1B1 were examined, showing identical genotypes to pre‐transplantation DNA. Short tandem repeat analysis showed that the buccal swab contained DNA from both donor and recipient. It was estimated that the buccal swab contained ~63% donor DNA, while DNA from hair follicles showed 0% donor DNA. In conclusion, pharmacogenetic profiling after allogenic HSCT should be done with consideration. Analysis of pre‐transplant peripheral blood is preferred over buccal swab due to the presence of donor DNA contamination. DNA extracted from hair is also a reliable source; however, application might be restricted due to limited DNA yield.